The evaluation of medical plant and chemical supplementation effects on anaerobic power in handball players - Sajedi, H.; Salari, N.; Bas, M.; Bayram, M. (Sport Science - International Scientific Journal of Kinesiology, 2016)
The aim of this study was to investigate the effects of ginseng and glutamine supplementation on peak and mean anaerobic power output. Handball players (n=40) were volunteered for this study. Weight and height of the players were measured and the age range was between 17-24 years old (20.7±4.3). The Experimental Group (n=20) that n=10 for ginseng supplementation and n=10 for glutamine supplementation was given glutamine treatment of 0.3g/kg/day of glutamine for a period of six weeks and 400 mg ginseng daily. Control Group (n=20) for two supplementations had no treatment. Each participant performed the Wingate Test on a Monark 894e arm ergometer. Peak power and mean power were determined as the highest and average power achieved during any 30s of the test. There was a significant effect (p<0.05) of the supplementations on Wmax producing a higher value post-test than the pre-test. The ginseng supplement had more significant effects (p<0.05) on the mean and peak power under anaerobic circumstances in compare to the glutamine supplementation. It concluded to suggest other dosages of ginseng and glutamine should be investigated. Further research could assess the influence of ginseng and glutamine intake and intensive physical exercise involving athletes of other sports and using other performance traits, such as athletic skill elements.